2008
DOI: 10.1136/jnnp.2008.157792
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative preservation of corticospinal function in the brainstem

Abstract: MEP monitoring-as opposed to SEPs-is a valid indicator of corticospinal function in brainstem-related surgery, independent from the type of lesion operated on. New deficit occurs only after more pronounced MEP changes than in supratentorial surgery, but complete loss as in spinal surgery is not required. MEPs may help to prevent permanent new paresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 39 publications
(40 reference statements)
2
18
0
3
Order By: Relevance
“…The criterion adopted in our study lead to a warning issued in 39 surgical interventions (38%). This rate of significant MEP changes is in-between those of two previous studies on MEP in brainstem surgery (46% [12], 22% [3]). The warning rate may partly depend on the number of children in the patient population, as children require higher MEP thresholds [6].…”
Section: Mep Warning Criteria In Brainstem Surgerysupporting
confidence: 63%
See 2 more Smart Citations
“…The criterion adopted in our study lead to a warning issued in 39 surgical interventions (38%). This rate of significant MEP changes is in-between those of two previous studies on MEP in brainstem surgery (46% [12], 22% [3]). The warning rate may partly depend on the number of children in the patient population, as children require higher MEP thresholds [6].…”
Section: Mep Warning Criteria In Brainstem Surgerysupporting
confidence: 63%
“…Furthermore, it has been shown that sensitive warning criteria trigger surgical reevaluation earlier [1,12]. The criterion adopted in our study lead to a warning issued in 39 surgical interventions (38%).…”
Section: Mep Warning Criteria In Brainstem Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Bei der ersten Gruppe von Verfahren, dem eigentlichen Monitoring, wird die Funktion der Nervenbahnen kontinuierlich überwacht [12,[14][15][16][17][18][19][20]. Die Messungen werden jeweils sofort ausgewertet, indem sie mit den Ausgangswerten zu Beginn der Operation verglichen werden (Abbildung 1).…”
Section: Monitoring: Verfahren Des Ionm Zur Kontinuierlichen üBerwachunclassified
“…Bei intrakraniellen Eingriffen wird schon eine Amplitudenreduktion als Warnzeichen angesehen [18]. Bei Eingriffen am Hirnstamm werden optimale Warnkriterien noch diskutiert [19,20,29] .…”
Section: Die Intraoperativen Meps Dienen Zur üBerwachung Der Muskelakunclassified